Methods Used to Investigate the Plasmodium falciparum Digestive Vacuole - Edgar, Rebecca C. S.; Counihan, Natalie A.; McGowan, Sheena; de Koning-Ward, Tania F. (Frontiers in Cellular and Infection Microbiology, 2022)
Plasmodium falciparum malaria remains a global health problem as parasites continue to develop resistance to all antimalarials in use. Infection causes clinical symptoms during the intra-erythrocytic stage of the lifecycle where the parasite infects and replicates within red blood cells (RBC). During this stage, P. falciparum digests the main constituent of the RBC, hemoglobin, in a specialized acidic compartment termed the digestive vacuole (DV), a process essential for survival. Many therapeutics in use target one or multiple aspects of the DV, with chloroquine and its derivatives, as well as artemisinin, having mechanisms of action within this organelle. In order to better understand how current therapeutics and those under development target DV processes, techniques used to investigate the DV are paramount. This review outlines the involvement of the DV in therapeutics currently in use and focuses on the range of techniques that are currently utilized to study this organelle including microscopy, biochemical analysis, genetic approaches and metabolomic studies. Importantly, continued development and application of these techniques will aid in our understanding of the DV and in the development of new therapeutics or therapeutic partners for the future.